(untitled) (Journal of Engineering, 2019)
The influence of adding metal foam fins on the heat transfer characteristics of an air to water double pipe heat exchanger is numerically investigated. The hot fluid is water which flows in the inner cylinder whereas the cold fluid is air which circulates in the annular gap in parallel flow with water. Ten fins of metal foam (Porosity = 0.93), are added in the gap between the two cylinder, and distributed periodically with the axial distance. Finite volume method is used to solve the governing equations in porous and non-porous regions. The numerical investigations cover three values for Reynolds number (1000 ,1500, 2000), and Darcy number (1 x10-1, 1 x10-2, 1x10-3). The comparison between the two case with and without insertion the metal foam fins are examined in this study. Results show that the temperature of the inner pipe wall is affected by the Reynolds number, water inlet temperature, Darcy number variation. The resulting values and the behavior of the local and average coefficient of heat transfer are presented. The improvement in the mean coefficient of heat transfer (hm) is found to be 129 % with the using of the metal foam fins.